Strategic Groups: Theory, Research and Taxonomy - THOMAS, Howard (Institutional Knowledge at Singapore Management University, 1986)
This paper discusses the concept of strategic groups, focusing upon the importance of intra-industry strategic groupings in understanding differences across firms within an industry. The problems involved in identifying strategic groups within industries are examined through a comprehensive review of recent studies. It is demonstrated that much of the research has used surrogates for elements of a firm's strategic direction, e.g. vertical integration, product range, R & D expenditure, to suggest bases by which creative and sustainable groups are formed. The authors argue that certain theoretical concepts such as mobility barriers, isolating mechanisms and controllable variablesprovide much firmer bases for identifying strategic groups within industries. Thus, taxonomies for understanding the nature of strategic group formulation can be developed. Implications of the strategic group concept for such strategic issues as the structure-performance linkage, firm mobility, patterns of rivalry, industry evolutionand firm growthare then examined. The paper concludes by indicating fruitful directions for strategic group research in the context of the strategic management field.